Strontium-doped calcium silicate bioceramic with enhanced in vitro osteogenic properties. (5th June 2017) - No, Young Jung; Roohaniesfahani, Seyediman; Lu, Zufu; Shi, Jeffrey; Zreiqat, Hala
Abstract: Gehlenite (GLN, Ca2 SiAl2 O7 ) is a bioceramic that has been recently shown to possess excellent mechanical strength and in vitro osteogenic properties for bone regeneration. Substitutional incorporation of strontium in place of calcium is an effective way to further enhance biological properties of calcium-based bioceramics and glasses. However, such strategy has the potential to affect other important physicochemical parameters such as strength and degradation due to differences in the ionic radius of strontium and calcium. This study is the first to investigate the effect of a range of concentrations of strontium substitution of calcium at 1, 2, 5, 10 mol% (S1-GLN, S2-GLN, S5-GLN and S10-GLN) on the physicochemical and biological properties of GLN. We showed that up to 2 mol% strontium ion substitution retains the monophasic GLN structure when sintered at 1450 °C, whereas higher concentrations resulted in presence of calcium silicate impurities. Increased strontium incorporation resulted in changes in grain morphology and reduced densification when the ceramics were sintered at 1450 °C. Porous GLN, S1-GLN and S2-GLN scaffolds (∼80% porosity) showed compressive strengths of 2.05 ± 0.46 MPa, 1.76 ± 0.79 MPa and 1.57 ± 0.52 MPa respectively. S1-GLN and S2-GLN immersed in simulated body fluid showed increased strontium ion release but reduced calcium and silicon ion release compared to GLN without affecting overall weight loss and pH over a 21 d period. The bioactivity of the S2-GLN ceramics was significantly improved as reflected in the significant upregulation of HOB proliferation and differentiation compared to GLN. Overall, these results suggest that increased incorporation of strontium presents a trade-off between bioactivity and mechanical strength for GLN bioceramics. This is an important consideration in the development of strontium-doped bioceramics.